A Novel Encryption Technique Using DNA Encoding and Single Qubit Rotations - Goswami, Partha Sarathi; Chakraborty, Tamal; Chatterjee, Harekrishna (International Journal of Computer Sciences and Engineering, 2025)
In today’s world security has become a major threat over the transmission channel. To overcome this DNA cryptography is used to encrypt and transfer the message from sender to receiver over a secured communication network. This paper focuses on the encryption and decryption of the message using DNA encoded sequences and discusses the cryptographic applications of single qubit rotations from the view of one-way trapdoor functions. For encryption quantum public key is used and for decryption the concept of classical private key is used. The mapping between integer numbers and quantum states is done using one way trapdoor function.